Short Communication: Carbon stock of mangrove forest in Pantai Sederhana, Bekasi District, West Java, Indonesia - IKKA ERNIASARI; ENDANG HERNAWAN; MULYANINGRUM MULYANINGRUM (Society for Indonesian Biodiversity, 2024)
Abstract. Erniasari I, Hernawan E, Mulyaningrum. 2024. Short Communication: Carbon stock of mangrove forest in Pantai Sederhana, Bekasi District, West Java, Indonesia. Biodiversitas 25: 2974-2980. Mangrove forests play an important role in the carbon cycle because this forest can store greater amounts of carbon than other ecosystems including tropical rainforests. Mangrove forests in Bekasi District, West Java, Indonesia have enormous potential to absorb carbon in this industrial area. In this research, we estimate the aboveground carbon (AGC), belowground carbon (BGC), and soil organic carbon (SOC) of mangrove forest in Pantai Sederhana, Muaragembong Subdistrict, Bekasi District. Carbon estimation of AGC and BGC was carried out using the allometric method, while SOC at four depth intervals (0-15, 15-30, 30-50, and 50-100 cm) was estimated using the LOI (Loss of Ignition) method. There were four mangrove species in Pantai Sederhana, namely Avicennia marina, Avicennia alba, Rhizophora apiculata, and Rhizophora mucronata. The total carbon stock was 329.54 Mg.C.ha-1, which was composed by aboveground carbon (114.51 Mg.C.ha-1), belowground carbon (61.46 Mg.C.ha-1) and soil carbon (153.56 Mg.C.ha-1). The largest carbon pool was contributed from soils with 47% of the total carbon stock. The result of this study can be used as the initial information of the importance of the mangrove ecosystem in Bekasi District.